The devil's grinder = Moara dracilor - Ionescu-Quintus, Mircea (Parmenides Publishing, 2013)
"First published in Romanian as Moara Dracilor in 1999 by Editura Ion Creang- S.A. This dual-language edition [is] published . . . with a new Foreword, a new Preface by the author, a new About the Translators, seven additional Poems, three new Illustrations, and a new author Biography"--